Comparing real-world outcomes of total neoadjuvant treatment and CRT at a tertiary medical center - Turfa, Rim; Alawabdeh, Tala; Naser, Ayman; Alamro, Yazan; Albliwi, Moath; Almasri, Sama; Al Qazakzeh, Abdullah; Shattal, Mohammad Abu; Dabous, Ali; Amarin, Rula (Frontiers in Oncology, 2023)
For years, standard treatment for locally advanced rectal cancer (LARC) has included neoadjuvant chemoradiotherapy (CRT), followed by surgery and adjuvant chemotherapy. Although CRT has helped reduce local recurrence rates, it hasn't consistently improved overall survival. Recent trials have unveiled a different approach called total neoadjuvant treatment (TNT), involving pre-surgery radiotherapy followed by chemotherapy ( CAPOX/FOLFOX). TNT shows promise with improved treatment response and lower distant metastasis rates without compromising local control. Consequently, many healthcare institutions have adopted TNT as their preferred neoadjuvant treatment. This study, conducted at a tertiary center, compares the real-world outcomes of both CRT and TNT protocols.